Unprecedented levels of ultrafine particles, major sources, and the hydrological cycle - Wolfgang Junkermann (Scientific Reports, 2022)
Abstract Ultrafine particles (UFP) acting as cloud condensation nuclei (CCN) are the driving force behind changing rainfall patterns. Recently observed weather extremes like floods and drought might be due to changing anthropogenic UFP emissions. However, the sources and budgets of anthropogenic primary and secondary particles are not well known. Based on airborne measurements we identified as a major contribution modern fossil fuel flue gas cleaning techniques to cause a doubling of global primary UFP number emissions. The subsequent enhancement of CCN numbers has several side effects. It’s changing the size of the cloud droplets and delays raindrop formation, suppressing certain types of rainfall and increasing the residence time of water vapour in the atmosphere. This additional latent energy reservoir is directly available for invigoration of rainfall extremes. Additionally it’s a further contribution to the column density of water vapour as a greenhouse gas and important for the infrared radiation budget. The localized but ubiquitous fossil fuel related UFP emissions and their role in the hydrological cycle, may thus contribute to regional or continental climate trends, such as increasing drought and flooding, observed within recent decades.